The challenge of biological control of Cosmopolites sordidus Germar (Col. Curculionidae): A review. (2nd February 2021) - Tresson, Paul; Tixier, Philippe; Puech, William; Carval, Dominique
Abstract: The banana weevil (also known as banana root borer) Cosmopolites sordidus Germar (Coleoptera Curculionidae) is the major pest of banana and plantain. Because banana ranks 2nd in fruit production worldwide, this pest has substantial social and economic importance. The biological control of the C. sordidus remains challenging because of its behaviour and resistance to parasitism and predation. The last review concerning the biological control of C. sordidus was published two decades ago, and relevant knowledge and methods have developed in the interim. The present paper provides an update of that knowledge and summarizes past and current challenges as well as providing perspectives on achieving sustainable control of C. sordidus . We first discuss studies on the classical biological control of C. sordidus, underlining the limits of classical biological control methods such as the importation of predators, parasitoids or pathogens. Next, we consider conservation biological control of C. sordidus, with a focus on ants. We also highlight an 'arthropod bias' that has led to a lack of information on the role of vertebrates in the regulation of C. sordidus .